Drawn into violence: Evidence on what makes a criminal from the Vietnam draft lotteries - Jason M. Lindo; Charles Stoecker (Institute for the Study of Labor (IZA), 2010)
Draft lottery number assignment during the Vietnam era provides a natural experiment to examine the effects of military service on crime. Using exact dates of birth for inmates in state and federal prisons in 1979, 1986, and 1991, we find robust evidence of effects on violent crimes among whites. In particular, we find that draft eligibility increases incarceration rates for violent crimes by 14 to 19 percent. Based on Angrist and Chen's (2008) estimate of the effect of draft eligibility on veteran status, these estimates imply that military service increases the probability of incarceration for a violent crime by 0.27 percentage points. Results for nonwhites are not robust. We conduct two falsification tests, one that applies each of the three binding lotteries to unaffected cohorts and another that considers the effects of lotteries that were not used to draft servicemen.
Keywords: K42; H56; 330; crime; violence; military; two-sample IV; Vietnam War; Kriminalität; Wehrdienst; Soldaten; USA; Krieg; Feldforschung; Vietnam